2022
DOI: 10.1002/pits.22655
|View full text |Cite
|
Sign up to set email alerts
|

Asian American adolescents' mental health literacy and beliefs about helpful strategies to address mental health challenges at school

Abstract: Asian Americans are the fastest-growing racial group in the United States. Contrary to the model minority myth, many Asian American youth experience mental health challenges. However, they are less likely to utilize school-based mental health services than their non-Asian American peers. A paucity of research addresses Asian American adolescents' understanding of mental health disorders and beliefs about helpful strategies for addressing psychological challenges within the school context. The present study uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…The other seven studies described the role of school-based services in influencing Asian immigrant youth’s mental health and well-being and how services are accessed [ 122 , 131 , 137 , 139 , 154 , 157 , 158 ]. Several studies found that Asian immigrant youth, controlling for confounders, had significantly lower odds of using their school-based MHSU prevention program than Black or Latino youth [ 131 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other seven studies described the role of school-based services in influencing Asian immigrant youth’s mental health and well-being and how services are accessed [ 122 , 131 , 137 , 139 , 154 , 157 , 158 ]. Several studies found that Asian immigrant youth, controlling for confounders, had significantly lower odds of using their school-based MHSU prevention program than Black or Latino youth [ 131 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
“…For those who did access services, relationships with school health program staff and their ability to refer to relevant school health programs served as key factors influencing youths’ openness to engage in stigmatized services, such as contraception counselling or mental health therapy [ 131 , 154 ]. Furthermore, initiating school-based to promote mental health awareness [ 157 ] and programs that address the intersection of traditional and American values were recommended to improve MHSU literacy and service access in school settings [ 158 ]. It was recommended that teachers and administrators should also strive to create a positive school environment by encouraging the development of supportive relationships among students, their peers, and their teachers [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…Understanding mental health literacy in Asian-American adolescents can be supplemented with a clarification of mental health risk factors in Asian-American youth. Culturally-specific examples include the internalization of the model minority stereotype, high academic pressure, and sociocultural beauty standards (Liu, J. et al, 2022). Institutional involvement, such as through school mental health professionals, may be a key resource to improving Asian-American adolescent mental health literacy and improve help seeking behavior.…”
Section: Adolescentsmentioning
confidence: 99%
“…Creating a culture in which it is standard practice for every student to regularly see a counselor, whether or not they are in crisis, can normalize mental health help-seeking and destigmatize psychotherapy through positive experiences with the mental health system. Additionally, when communities integrate mental health services in the academic system, students and the greater community gain increased mental health literacy (Cheng et al, 2018; Liu et al, 2022).…”
Section: Increasing Access To Mental Health Servicesmentioning
confidence: 99%